Challenges and resources in adult life with Joubert syndrome: issues from an international classification of functioning (ICF) perspective. Issue 18 (28th August 2022) - Romaniello, Romina; Gagliardi, Chiara; Desalvo, Patrizia; Provenzi, Livio; Battini, Roberta; Bertini, Enrico; Bonati, Maria Teresa; Briguglio, Marilena; D'Arrigo, Stefano; Dotti, Maria Teresa; Giordano, Lucio; Macaluso, Claudio; et al.
Abstract: Background: Joubert Syndrome (JS) is a rare inherited neurodevelopmental disorder defined by a characteristic cerebellar and brainstem malformation (i.e. the molar tooth sign) and variable organ involvement. The aim of the present study was to describe functional limitations and disabilities in a large sample of adult patients with a diagnosis of JS. Methods: We administered the International Classification of Functioning (ICF) checklist to thirty-six adult Italian patients with JS or their caregivers through telephone calls. Results: None-to-mild impairment was documented for basic cognitive and mental functions, whereas severe deficit emerged for higher-order skills and language. A mismatch between individuals' capacity for daily activity and social participation and the actual performance in these fields emerged, suggesting that adults with JS may greatly benefit from external support from the caring environment. Indeed, specific facilitators were highlighted, including communication technologies as well as family members, healthcare professionals and peers support. Mild-to-severe barriers have been identified by adult patients with JS in the domains of services, systems and policies. Conclusions: These findings highlight challenges and barriers for adults with JS in areas of daily functioning that may be improved by investing in rehabilitation care models that embed social support programs and policies into clinical interventions. IMPLICATIONS FOR REHABILITATION: Children with Joubert Syndrome, a child-onset rare inherited neurodevelopmental condition, are growing up and becoming adults; a life course approach in rehabilitation is needed; There is a substantial lack of information on the long-term adaptive daily functioning of children with a diagnosis of Joubert Syndrome; In this paper, the International Classification of Functioning (ICF) was applied to assess the daily functioning in people with JS; Severe deficits emerged for high-order skills and language, whereas the use of communication technologies and the engagement of family members were highlighted as key facilitators; These findings highlight the need for a change of paradigm in the care model of subjects with JS, with the embedding of social support in rehabilitation programs.